Channeling Science Information Seekers' Attention? A Content Analysis of Top‐Ranked vs. Lower‐Ranked Sites in Google1. Issue 3 (14th November 2013) - Li, Nan; Anderson, Ashley A.; Brossard, Dominique; Scheufele, Dietram A.
Abstract Researchers have suggested that search engines shape portrayals of information by making large and popular websites more prominent while discriminating against smaller sites. Despite the possible skew of information sources, little empirical work has examined whether there is consistent dominance of content representative of that in highly ranked web links provided by search engines. We conducted a content analysis of a particular issue—nanotechnology—in Google and found that the very top‐ranked Google results are likely to feature the technical‐, environmental‐, and risk‐related aspects of nanotechnology. We compared this to lower‐ranked search results and found emphasis on significantly different themes. The implications of Google as a market‐dominant search engine on the diversity of online science content are discussed.